1977
DOI: 10.1152/jappl.1977.42.5.728
|View full text |Cite
|
Sign up to set email alerts
|

Urinary catecholamine excretion on induction to high altitude (3,658 m) by air and road

Abstract: In a preliminary pilot study we had reported a significant difference in urinary catecholamine excretion between symptomatic and asymptomatic individuals inducted to high altitude by air. The present study covers slower induction by road; 25 lowlanders ascended from 1,800 to 3,658 m in 50 h and 33 similar subjects covered the journey in 6 h. They were studied according to the protocal used in the initial study. None of the 58 subjects inducted by road developed symptoms of high-altitude illness. Their urinary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…A loss of sensitivity of the sinus node secondary to excessive sympathetic neurohumoral activity has been proposed to be one of the factors at the origin of reduced LF in heart failure (5). Increased neural and humoral sympathetic activities have been reported as features of established AMS (4,11,21). We may speculate that, as in heart failure, a loss of sensitivity of the sinus node secondary to excessive and more sustained sympathetic neurohumoral activity could explain the blunted LF RR NU we observed in subjects with AMS.…”
Section: Cardiovascular Variability and Amsmentioning
confidence: 53%
See 1 more Smart Citation
“…A loss of sensitivity of the sinus node secondary to excessive sympathetic neurohumoral activity has been proposed to be one of the factors at the origin of reduced LF in heart failure (5). Increased neural and humoral sympathetic activities have been reported as features of established AMS (4,11,21). We may speculate that, as in heart failure, a loss of sensitivity of the sinus node secondary to excessive and more sustained sympathetic neurohumoral activity could explain the blunted LF RR NU we observed in subjects with AMS.…”
Section: Cardiovascular Variability and Amsmentioning
confidence: 53%
“…A marked increase in peripheral sympathetic activity is a common feature of mountain sickness (4,11) and has also been suggested to contribute to the genesis of high-altitude pulmonary edema (4). Whether autonomic hyperactivation may play a role in the genesis of AMS is not known.…”
mentioning
confidence: 99%
“…Loeppky et al (2003) inferred higher sympathoadrenergic tone due to elevated plasma levels of plasma epinephrine in AMS following 12 h of simulated altitude exposure in a decompression chamber. Hoon et al (1976) observed a significant increase in urine catecholamine excretion in individuals with AMS following rapid transport to altitude. Interestingly, the maximal increase in catecholamine excretion occurred after a week spent at altitude where most individuals became asymptomatic.…”
Section: Discussionmentioning
confidence: 79%
“…An increase in catecholamine excretion associated with a rise in sympathetic nerve activity in response to altitude has been suggested to be involved in the development of AMS (Hoon et al 1976;Loeppky et al 2003). Loeppky et al (2003) inferred higher sympathoadrenergic tone due to elevated plasma levels of plasma epinephrine in AMS following 12 h of simulated altitude exposure in a decompression chamber.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation